Aberrant frontolimbic circuit in female depressed adolescents with and without suicidal attempts: A resting-state functional magnetic resonance imaging study - Liu, Mengqi; Huang, Yang; Li, Xuemei; Liu, Yang; Yu, Renqiang; Long, Yicheng; Lv, Fajin; Zhou, Xinyu (Frontiers in Psychiatry, 2022)
Background: The neurobiological basis of suicidal behaviors among female adolescents with major depressive disorder (MDD) remains largely unclear. Methods: Fifty-eight drug-naïve, first-episode female adolescent MDD (including 31 patients with suicidal attempt (SA group), and 27 patients without SA (non-SA group)), and 36 matched healthy controls (HC) participated in the present study. Resting-state functional MRI was performed on each subject. The metrics of the amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF), and regional homogeneity (ReHo) were compared among the three groups. Then seed-based functional connectivity (FC) was conducted based on the ALFF/fALFF and ReHo results, which were then correlated to clinical variables. Results: Compared with the non-SA group, the SA group exhibited increased fALFF in the bilateral insula and right precentral gyrus, and enhanced ReHo in the left superior temporal gyrus, left middle cingulate cortex, right insula, and right precentral gyrus. Relative to the HCs, the SA group demonstrated additionally reduced fALFF and ReHo in the left middle frontal gyrus. Moreover, the SA group showed increased FC between the right precentral gyrus and the left middle frontal gyrus and left insula, and between the right insula and anterior/middle cingulate cortex compared to the non-SA and HC groups. In addition, the fALFF in the left middle frontal gyrus was positively correlated with the 17-item Hamilton Depression Rating Scale scores, and the values in the fALFF/ReHo in the right insula were positively correlated with the duration of MDD within the patient group. Conclusions: These findings highlight the multiple abnormalities of the frontolimbic circuit, which may enhance our understanding of the neurobiological basis underlying female MDD with SA during adolescence.